Level Of Math Problem Solving Proficiency Grade V SDN 2 Kalirejo On Fractional Story Problem - Marita Cahya Purnama; Tri Yuniantari Redyoningrum; Liftahul Sekar Aji; Moh Salimi (Universitas Sebelas Maret, 2019)
In mathematics, students' ability to solve problems is very much needed. Every student has different abilities. For this reason, it is necessary to conduct a research in order to find out the students' abilities in solving problems in mathematics, especially in fractional material. In researching, quantitative description is the method chosen by the researcher. In this study using a research instrument in the form of a test to measure students' ability to solve mathematical problems and conducted interviews. Data analysis of the results of mathematical tests about solving fractions of fifth grade students at SD Negeri 2 Kalirejo is in the high category. This is evident from the results of tests at SD Negeri 2 Kalirejo that included in the high category were 61.29%, moderate were 23.80% and the low and very low categories were 12.89%.